Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
[tex]f(x)=9x+7\\
y=9x+7\\
9x=y-7\\
x=\dfrac{1}{9}y-\dfrac{7}{9}\\
f^{-1}(x)=\dfrac{1}{9}x-\dfrac{7}{9}\\[/tex]
Applying it's definition, the inverse of the function f(x) = 9x + 7 is given by:
[tex]f^{-1}(x) = \frac{x - 7}{9}[/tex]
How to find the inverse of a function?
Suppose we have a function y = f(x). To find the inverse function, we exchange x and y in the original function, then isolate f.
In this problem, the function is:
y = 9x + 7
Exchanging:
x = 9y + 7
Isolating y:
9y = x - 7
[tex]y = \frac{x - 7}{9}[/tex]
[tex]f^{-1}(x) = \frac{x - 7}{9}[/tex]
More can be learned about inverse functions at https://brainly.com/question/8824268
#SPJ2
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.